COVID-19 knowledge, attitude, and practice of United Arab Emirates heath providers at the start of the pandemic 2020 - Aljazia Khalfan Alghfeli; Amal Abdul Rahim Al Zarooni; Hamda Musabbah Alremeithi; Roqayah Abdulla Almadhaani; Latifa Baynouna Alketbi (BMC, 2023)
Abstract Background Early in 2020, healthcare providers faced the novel virus COVID-19 that had unprecedented risk to them and the community they serve. With COVID-19 high infectivity rate and considerable morbidity and mortality, healthcare providers ' precautionary practices to protect themselves, colleagues, and patients were determinantal to provide safe health services. This study aims to assess the knowledge, attitude, and practice of healthcare providers in the United Arab Emirates toward COVID-19 and to examine its determinants. Method This cross-sectional study was conducted to assess COVID-19 knowledge, attitudes, and practice (KAP) of healthcare providers in the Emirates of Abu Dhabi, the United Arab Emirates, from April to July 2020, using an online anonymous self-administered questionnaire. A convenient sampling method was used to distribute the online survey link through the organization's email network admin list and smartphone messaging. Descriptive statistics, t-tests, and multivariant linear regression were used. Results A total of 2371 healthcare providers responded to the survey. A total of 1091 worked in inpatient hospitals, 494 in primary health care, and 388 in emergency and ICU care. The overall performance score for all healthcare providers was as follows: 49.1%, poor score; 41.8%, intermediate score; and 9.2%, good score with a mean result of 17.14. Factors leading to better overall performance scores were years of experience, pediatricians' specialty, and specialist occupation. A total of 55.7% received good direct knowledge from all healthcare providers. In practice, 48% had good practices toward COVID-19. The overall attitude mean was 2.8, with a maximum score of 7, indicating a positive attitude toward COVID-19. Conclusions Although this study describes a dynamic learning status and could reflect the early pandemic situation in Abu Dhabi health care, it does provide a method to assess the precursor of the critical outcome. It is recommended to follow this study with an assessment of the training program targeting all healthcare providers to ensure a better response to emerging infections.